DIFS Modifications to Support QoS in IEEE 802.11g DCF Ad-hoc Networks - Md Khambari, M. N.; Sahib, S.; Othman, M. F. I. (2009)
This paper describes and investigates the QoS provisioning technique used in IEEE 802.11g ad-hoc structure. This research then propose better scheme to support QoS by modifying the DCF Interframe Space (DIFS) to use new values to bias towards the high priority traffic flow and distinguish it from the low priority traffic. Simulations are done using NS-2 and the findings presented. Results showed that better throughput can be achieved to provide better traffic flows on high priority traffic.